Hyperglycemic condition influence on mineral trioxide aggregate biocompatibility and biomineralization - de Azevedo Queiroz, Índia O. [UNESP]; Gonçalves, Luanna O. [UNESP]; Takamiya, Aline S. [UNESP]; Rezende, Gabriely C. [UNESP]; Machado, Thiago [UNESP]; Siveiri-Araujo, Gustavo [UNESP]; Ervolino, Edilson [UNESP]; Oliveira, Sandra Helena Penha de [UNESP]; Gomes-Filho, João E. [UNESP] (Wiley, 2019)
This study aimed to investigate in vitro and in vivo the influence of hyperglycemic condition on biocompatibility and biomineralization of gray mineral trioxide aggregate (GMTA) and white mineral trioxide aggregate (WMTA). For the in vitro study, fibroblast-like cells L929 were cultured under high or normal glucose concentration to investigate the effects of both MTA's on cell proliferation and inflammatory cytokines production IL-1β, IL-6, and TNF-α. For the in vivo study, polyethylene tubes containing MTA materials and empty tubes were implanted into dorsal connective tissues of Wistar rats previously assigned normal and hyperglycemic. After 7 and 30 days, the tubes with surrounding tissues were removed and subjected to histological, fluorescence and immunohistochemical analyzes of IL-1β, IL-6, and TNF-α. In vitro study showed that, under high glucose condition, GMTA reduced cell proliferation and IL-6 production compared with WMTA. Moreover, in vivo study revealed that hyperglycemic condition did not modify the inflammatory response and cytokines production in the tissue close to both materials. Independently of hyperglycemic status, mineralized areas were observed with both materials, but the fluorescence intensity of WMTA was diminished on 14 days in hyperglycemic animals. It is possible to conclude that GMTA was able to inhibit the proliferation rate and IL-6 production under high glucose concentration in vitro. Furthermore, cytokines production and inflammatory response were not upregulated in hyperglycemic animals; however, a decrease in the calcium deposition was observed in presence of WMTA, suggesting a delay in the mineralization process.
Keywords: cytokines; gray MTA; hyperglycemia; mineralization; white MTA